The Effects of Mulligan's Mobilization with Movement Techniques in Patients with Lateral Epicondylitis. - Cakmak, Aycan; Dereli, Elcin; Sindel, Dilsad (Wiley, 2014)
[Abstract Not Available]
78th Annual Meeting of the American-College-of-Rheumatology (ACR) / 49th Meeting of the Association-of-Rheumatology-Health-Professionals (ARHP) -- NOV 14-19, 2014 -- Boston, MA